RESPONS PERTUMBUHAN DAN PRODUKSI KEDELAI (Glycine max L. (Merill)) DI LAHAN KERING TERHADAP INOKULASI Bradyrhizobium japonicum YANG DIINDUKSI GENISTEIN DAN PEMBERIAN PUPUK ORGANIK - Yuda P Surbakti1; Yaya Hasanah; Lisa Mawarni (Universitas Sumatera Utara, 2014)
Effort to increase soybean production in dryland experiencing problems such as nutrientdeficiencies. Alternative attempt to resolve the issue that inoculation of B. japonicum is able tofixate free N2 in the atmosphere that can be utilized by soybean plants. In this symbiosis requiredisoflavone genistein is a signal molecule for nodulation. The objective of this research was knowthe respons of growth and production of soybean (Glycine max L. Merill.) on dryland withapplication of inoculation B. japonicum induced genistein and organic fertilizer. This research wasconducted at Desa Sambirejo Kecamatan Binjai Kabupaten Langkat on June - October 2012, usinga randomized block design factorial with two factors. The first factor was isoflavon (genistein)consisted of without genistein and with genistein. The second factor was combination ofB. japonicum with organic fertilizer consisted of without B. japonicum; B. japonicum;B. japonicum + fertilizer organic (10 ton/ha); B. japonicum + rice straw compost (10 ton/ha);B. japonicum + fertilizer organic (5 ton/ha) + rice straw compost (5 ton/ha). Parameters observedwere shoot dry weight, root dry weight, seed dry weight per plant, and dry weight of 100 seeds.The result showed that induction of genistein tends to increase shoot dry weight, root dry weight,seed dry weight per plant, dry weight of 100 seeds, combination B. japonicum and rice strawcompost to increase dry weight of 100 seeds, and the interaction between genistein and combinationB. japonicum and rice straw compost tends to increase root dry weight and dry weight of 100 seeds.Key words: B. japonicum, genistein, growth, production, soybean